Use of Multiferroic Materials in Patch Antenna Design - Zervos, T.; Stamopoulos, D.; Lazarakis, F.; Alexandridis, A.A.; Pissas, M.; Giannakopoulou, T.; Dangakis, K.; IEEE (2009 3RD EUROPEAN CONFERENCE ON ANTENNAS AND PROPAGATION, VOLS 1-6, 2009)
In this paper we introduce the utilization of novel compounds that can be magnetoelectric, namely Al(2-x)FexO(3) and Ga2-xFexO3, or ferrimagnetic, namely Y3Fe5O12, as effective constituents in patch antennas. Owing to their coupled dielectric and magnetic properties these constituents can probably tune the radiation characteristics of the patch antenna by means of an externally controlled parameter such as a magnetic and/or electric field. We clearly demonstrate that using Y3Fe5O12 in the antenna substrate, the type and the sense of the antenna polarization is strongly influenced by applying an external magnetic field.